The NAAAA: Ten Years Old and Changing - Mand, Brian; Fletcher, Harold J. (My University, 1986)
This paper reviews results of a survey of 72 Division I athletic advisors who completed it at the 1986 national convention (10 year anniversary of N4A). It includes demographic and salary information, job responsibilities (checklist out of 37 items), unit budgets, and reporting lines. Findings show that veteran advisors were male, over 30, with coaching experience especially in revenue sports, and newer advisors were women, who tended to be younger with no coaching experience.
Keywords: demographics; N4A